Optimalisasi Penggunaan WhatsApp Group Sebagai Sarana Komunikasi dan Media Pembelajaran Online Selama Masa Pandemi COVID-19 bagi Guru SD Negeri 10 Pianggu - Fitri Handayani; Marsika Sepyanda; Risza Dwiputri; Riyen Permata; Zulfariati (ASOSIASI IDEBAHASA KEPRI, 2021)
The readiness of elementary school teachers to use online learning media during the COVID-19 pandemic remains very low. Many teachers are unable to optimize various features of online teaching media, such as the use of WhatsApp. This was also experienced by teachers at SD Negeri 10 Pianggu, IX Koto Sungai Lasi sub-district. Not all teachers can make the best use of WhatsApp as an online learning tool. Some teachers are still unaware of the features accessible on WhatsApp that might be utilized as a learning assistance tool. Therefore it is necessary to provide training for teachers at SD Negeri 10 Pianggu, IX Koto Sungai Lasi sub-district in presenting learning materials through the use of WhatsApp. The implementation of service activities is carried out by providing training through lectures, discussions, and practices. Teachers were given information and knowledge about WhatsApp as a means of online learning medium during the Covid-19 pandemic. Based on the training activities that were conducted, the teachers demonstrated an eager attitude and a desire to learn more about various features on Whatsapp. Teachers receive training materials fast and can utilize the WhatsApp group as an effective online teaching tool, so the training generates favorable feedback.